2006
DOI: 10.1055/s-2006-950205
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Alkynylation Reactions to Aldehydes: The Effects of Aromatic Substituents upon the Enantioselectivity

Abstract: Asymmetric alkynylation reactions to linear alkyl and substituted aromatic aldehydes have been accomplished in good yields and with a range of selectivities. For aromatic aldehydes we observed that the selectivity of the alkynylation reaction appears to depend upon the substituents on the aromatic ring. Thus with electron-withdrawing substituents both the yield and enantioselectivities were good to excellent. In contrast to this, the presence of electron-donating groups provided excellent conversions; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A comparison of 4-fluorobenzaldehyde (entry 4), with the corresponding meta derivative (entry 5) reveals a significant 38% enhancement in yield and a modest improvement in the enantioselectivity of the reaction. Propargylation of the 3,5-dihalogenated benzaldehydes (entries [11][12][13][14] all occurred in excellent yields and enantiomeric excesses, however, we again observed an increase in the yield as the electronegativity of the 3,5-substituents decreased. Interestingly the ideal substrate, in terms of yield and enantiomeric excess, was 4-(trifluoromethyl)benzaldehyde (entry 10), which provided the propargyl alcohol (R)-25 in virtually quantitative yield and enantiomeric excess.…”
Section: Entrymentioning
confidence: 77%
See 3 more Smart Citations
“…A comparison of 4-fluorobenzaldehyde (entry 4), with the corresponding meta derivative (entry 5) reveals a significant 38% enhancement in yield and a modest improvement in the enantioselectivity of the reaction. Propargylation of the 3,5-dihalogenated benzaldehydes (entries [11][12][13][14] all occurred in excellent yields and enantiomeric excesses, however, we again observed an increase in the yield as the electronegativity of the 3,5-substituents decreased. Interestingly the ideal substrate, in terms of yield and enantiomeric excess, was 4-(trifluoromethyl)benzaldehyde (entry 10), which provided the propargyl alcohol (R)-25 in virtually quantitative yield and enantiomeric excess.…”
Section: Entrymentioning
confidence: 77%
“…10 Most recently we disclosed the results from our investigations into a range of asymmetric alkynylation reactions of aldehydes. 11 During the course of our investigations we observed that the enantioselectivity and, to a lesser degree, the efficiency of the alkynylation reaction appeared to be sensitive to the nature of the aromatic substituents that were present in the substrates based upon the salicylaldehyde derivative 3 ( Figure 1).…”
mentioning
confidence: 82%
See 2 more Smart Citations